Foreigners as actors of Europeanisation: Theoretical Conceptualisations for Research on Polish Cities (Politeja, 2022)
The article presents the conceptualisations that constitute the theoretical basis of a new study pursuing sociological understanding of some major social changes which have affected Polish cities in recent years. Poland has increasingly aligned itself with European countries in terms of political, socio-economic and cultural development. New flows of international immigration, meaning new individuals choosing Poland as the country where to work and settle, are making Polish cities more diverse and complex, both in a material and in a cultural way. The new research focuses on the role of foreigners as actors of urban diversification in Poland, analysing features of globalising cities, processes of Europeanisation, migrants’ discursive categorisation and anchoring. The article is conceived as a selection of critical problematisations.